A COMPARISON OF EUROPEAN AND AMERICAN GUIDELINES TO GAUGE THE PREVALENCE OF HYPERTENSION IN 16–19 YEAR OLD BLOOD DONORS. (June 2022) - Eason, Stephen; Sayers, Merlyn
Abstract : Objective: Against the background of increasing risk for hypertension in adolescents, we decided to investigate blood donation as an opportunity to compare national guidelines for identification of individuals, between 16–19 years of age, meeting hypertension criteria. Design and method: 16–19 year old volunteers donating blood between 2015 and 2020 were enrolled. They were asked to identify their ethnicity. Those declining were identified as "other''. Blood pressure was measured using automated equipment (Welch Allyn, ProBP). We compared the European Society of Cardiology/European Society of Hypertension (ESC/ESH) guidelines for hypertension (> = 140/90 mmHg) with the American College of Cardiology/American Heart Association (ACC/AHA) guidelines for hypertension (> = 130/80 mmHg). Results: There were 71912 participants, 63.2% (45441) and 36.8% (26471) were female and male respectively. Conclusions: More males, by comparison with females, met hypertension guideline criteria in all ethnicities. The prevalence of hypertension was highest in African Americans. Depending on which international hypertension criteria are chosen, there are significant differences in the size of population of 16–19 year olds identified for attention. Determining a suitable threshold that will justify investigation their investigation and treatment will require long term clinical trials.